Volume Equation and Table for Heritiera fomes (Buch.-Ham.) of the Sundarbans, Bangladesh - Hossain, Mahmood; Paul, Narottam; Siddique, Mohammad Raqibul Hasan; Rubaiot Abdullah, S. M.; Sanjoysaha,; Zaheer Iqbal, Md. (Indian Forester, 2019)
The Sundarbans mangrove forest is the single largest tract of mangrove forest in the world. Heritiera fomes (Buch.-Ham.) is the dominant species that covers 65% of the total merchantable timber of the Sundarbans. The objective of this study was to derive total volume (under bark) allometric model and volume table for H. fomes of the Sundarbans. Five allometric volume equations were tested to derive the allometric volume model. The best fit model was selected based on lowest value of Akaike Information Criterion (AIC), Residual Standard Error (RSE) and highest value of Coefficient of Determination (R2) and Akaike Information Criterion Weighted (AICw). The best fit volume model showed lowest values of AIC (12.1821), RSE (0.2485) and highest value of adjusted R2 (0.966) and AICw (0.7242) compared to the other models. The best fit model showed lower model prediction error (5 to 7%) and highest (0.864 to 0.988) values of model efficiency compared to the previous volume models of H. fomes for the Sundarbans. Finally, Ln (Vol) = -9.900593 + 0.9621471Ln (DÎ›2H) has appeared as best volume model compared to the previous models for H. fomes of the Sundarbans.